THE AL'GOFLORA SYSTEM: ENHANCING WATER TREATMENT PROCESSES THROUGH BIOLOGICAL OPTIMIZATION - Abjalov Alimardon Abdixomidovich (International Scientific and Current Research Conferences, 2024)
Water treatment facilities play a critical role in ensuring the supply of clean and safe water for human consumption and various industrial purposes. In recent years, there has been a growing emphasis on the integration of biological methods into water treatment processes to enhance efficiency and sustainability. This article explores the significance of the Al'GOFLORA system in optimizing water treatment processes by harnessing the power of algae and flora. Through a comprehensive review of literature and case studies, we highlight the multifaceted benefits of this innovative approach, ranging from improved nutrient removal to enhanced water quality and reduced energy consumption. The Al'GOFLORA system emerges as a promising solution for advancing the effectiveness and ecological sustainability of water treatment facilities.